MARK UP MARGIN DAN IMPLIKASINYA PADA PEMBIAYAAN MURABAHAH DI BAITUL MAAL WATTAMWIL - Bahrul Yaman; Heri Setiawan (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2013)
The purpose of this research is to analyze the influence of Third Party Fund, Non Performing Financing (NPF) and Financing Deposit to Ratio (FDR) toward Mark up margin and its implication to Murabahah Financing in BMT.. BMT study population is located in South Jakarta and Tangerang, which had stood at least 5 years and already have a good financial statements and according to standards that have been set. All sample was determined using convenience sampling, the samples were chosen based on the ease of obtaining data and not troublesome to measure and cooperative. This research used path analysis method with decomposition model. The result of substructure I indicate that Third Party Fund, Non Performing Financing (NPF) and Financing Deposit to Ratio (FDR) variabels have significantly effect to the Mark up margin. The result of substructure II indicate that Third Party Fund and Financing Deposit to Ratio (FDR) have significantly effect to the Murabahah Financing.DOI: 10.15408/sjie.v2i1.2371